Construção/desconstrução em nome de Arnaldo Antunes (uma obra de nosso tempo) - Silva, Marliane Dias (2011)
This work has as its object of study, the poems/songs multi-media Arnold Antunes, especially in its work hybrid NAME in which their art presents itself as project well 9 celebrated calls poetics post-modern. Intend, focus on their most significant aspects, those who approach the languages and require, for its analysis, the competition of several theories, put this to be the trait fundamental this form of text, because Arnaldo Antunes makes disclose, in the work in the agenda, the most authentic face of contemporary. In this way, far-that-be here an approach that mixing historical issues, aesthetic, social and philosophical, in order to outline a brief profile of the art of Antunes, as a model of significant contemporary art, the poet of multi-language and interdiscuss, the text of which falls between those who take place on a plurality of media, seats and expressions significantly intercommunicates. Talking in Post Modernity or Contemporary in refers to a rationale diachronic suggests a spacing of changes from one season to another or even the interruption of modernity, involving the emergence of a new all historical, with its own principles organizers and badges in all sectors of social life, including the gear, as in other times. Thus, the construction of identity in the era of post-modernity is related to a set of factors involving the social, historical and is expressed mainly in artistic. Such problems come, raising issues such as collective subjectivity, the brunt of the generations which consolidate the new forms of life in which we can note the fluidity of events and the discontinuity of things. Capture the meaning of these dimensions of man the new world, follow many languages that complement the urgency of the new times will be crucial for the analysis of the work NAME of Arnaldo Antunes.